2020
DOI: 10.2147/tcrm.s257714
|View full text |Cite
|
Sign up to set email alerts
|

<p>Managing Disease-Modifying Therapies and Breakthrough Activity in Multiple Sclerosis Patients During the COVID-19 Pandemic: Toward an Optimized Approach</p>

Abstract: The emergence of the novel coronavirus disease 2019 (COVID-19) pandemic has become a major public health challenge of global concern since December 2019, when the virus was recognized in Wuhan, the capital city of Hubei province in China and epicenter of the COVID-19 epidemic. Given the novelty of COVID-19 and the lack of specific anti-virus therapies, the current management is essentially supportive. There is an absence of consensus on guidelines or treatment strategies for complex disorders such as multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 92 publications
(104 reference statements)
0
23
0
Order By: Relevance
“…However, it should be noted that approximately one-quarter of the hospitalized cases in clinical trials had only moderate COVID-19. This suggests a potential referral bias likely driven by the general concern at the start of the pandemic and reflected in several guidelines, that patients on immunosuppressive/depleting drugs were at potential risk for severe disease and ocrelizumab infusions should be delayed ( Brownlee et al, 2020 ; Giovannoni et al, 2020 ; Hamdy et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that approximately one-quarter of the hospitalized cases in clinical trials had only moderate COVID-19. This suggests a potential referral bias likely driven by the general concern at the start of the pandemic and reflected in several guidelines, that patients on immunosuppressive/depleting drugs were at potential risk for severe disease and ocrelizumab infusions should be delayed ( Brownlee et al, 2020 ; Giovannoni et al, 2020 ; Hamdy et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hamdy et al suggested that DMD therapy should be discontinued in patients with active COVID-19 infection. 2 The Section of MS and Neuroimmunology of the Polish Neurological Society recommend discussing this issue with patients and consider their age, clinical condition and the type of DMD. 8 Therapy should be continued in the case of a mild course of the infection or during treatment with interferon, glatiramer, teriflunomide, dimethyl fumarate and in patients without lymphopenia (<800/ul).…”
Section: Discussionmentioning
confidence: 99%
“…3 The risk of infection differs in patients and can be increased by comorbidities and older age. 2 Infectious diseases may also lead to the deterioration of MS. The relationship between MS and COVID-19 is uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Fingolimod poses a moderate risk for COVID-19 infection. Alemtuzumab, rituximab, ocrelizumab, and cladribine continue to pose a significant risk [ 14 ]. Previous studies have shown that the overactivation of the innate immune response or an inadequate innate and adaptive immune response is associated with poorer outcomes [ 7 ].…”
Section: Discussionmentioning
confidence: 99%